DEMOCRATIC POLITICAL SYSTEM IN THE PERSPECTIVE OF MAQASID SHARIA : STUDY ANALYSIS OF YUSUF AL-QARADAWI’S THOUGHT - Athoilah Islamy; Sansan Ziaul Haq (AL IMARAH : JURNAL PEMERINTAHAN DAN POLITIK ISLAM, 2020)
Abstract: one of the big issue that is still debatable about the relationship between Islam and politics is how legitimate the democratic political system is in the paradigm of Islamic law. This study will explain the alternative paradigm in evaluating the democratic system based on the paradigm of Islamic law from a prominent Muslim intellectual named Yusuf al-Qaradawi. This research is a qualitative research in the form of literature review. The primary source used is a variety of literature that explains Yusuf al-Qaradawi's thoughts about democracy in Islam. The method used is the method of interpreting the thoughts of the figures with the maqasid al-shari‘ah approach. There are two big conclusions of this research. First, Yusuf al-Qaradawi's view of democracy can be said to be grounded in its epistemological foundation in understanding the concept of an Islamic state. For al-Qaradawi, an Islamic state is a system of government that provides policy improvisation space in the benefit of social, economic and political life based on the objectives of Islamic law (maqasid shari'ah). Second, Yusuf al-Qaradawi's view, the democratic system can be compatible with Islam if the principles in the democratic system are in accordance with various values which are the spirit of the objectives of Islamic law (maqasid shari'ah), such as the value of justice, equality of rights, freedom, etc. so. To realize this, the democratic system must carry a holistic vision and mission, which includes worldly and ukhrawi benefits as well as individual and social benefits.       Keywords: Validity, democracy, Yusuf al-Qaradawi, maqasid shari’ah;